2011
DOI: 10.1121/1.3596464
|View full text |Cite
|
Sign up to set email alerts
|

Particle motion measured at an operational wind turbine in relation to hearing sensitivity in fish

Abstract: The effect of sound pressure on the hearing of fish has been extensively investigated in laboratory studies as well as in field trials in contrast to particle motion where few studies have been carried out. To improve this dearth of knowledge, an instrument for measuring particle motion was developed and used in a field trial. The particle motion is measured using a neutrally buoyant sphere, which co-oscillates with the fluid motion. The unit was deployed in close vicinity to a wind turbine foundation at Utgru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
27
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 44 publications
(29 citation statements)
references
References 46 publications
0
27
0
1
Order By: Relevance
“…This has been reported by Tougaard et al (2009) for empirical data, and shown by Marmo et al (2013) using numerical modelling. Sigray and Andersson (2011) reported a change in the turbine output characteristics in relation to its operational state. They observed the largest amplitudes for a moderate wind speed at 6 ms À1 rather than at full operating wind speed, which differs from the findings of Lindell (2003) who obtained measurements at the same site, and found the highest levels to correspond with wind speed.…”
Section: A Applicability Of Datamentioning
confidence: 99%
See 4 more Smart Citations
“…This has been reported by Tougaard et al (2009) for empirical data, and shown by Marmo et al (2013) using numerical modelling. Sigray and Andersson (2011) reported a change in the turbine output characteristics in relation to its operational state. They observed the largest amplitudes for a moderate wind speed at 6 ms À1 rather than at full operating wind speed, which differs from the findings of Lindell (2003) who obtained measurements at the same site, and found the highest levels to correspond with wind speed.…”
Section: A Applicability Of Datamentioning
confidence: 99%
“…Some of the earlier studies, however, comprised longer term data collection, although data analysis concentrated on subsets of the measured data (e.g., Degn, 2000;Betke et al, 2004). One study focussed on particle a) Electronic mail: tanja.pangerc@npl.co.uk motion measurements from an offshore wind turbine (Sigray and Andersson, 2011).…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations